Suara Akar Rumput: Kebudayaan yang Mendasari Perilaku Ekonomi - Pratama, Yogi Pasca; Manzilati, Asfi - (Jurnal Ilmu Ekonomi dan Pembangunan, 2014)
Social values that are believed to individuals are often more than just maximizing profit motive alone that ultimately basing all economic interactions carried out in accordance moral owned economy and believed. Geographical location Wonosari village located on the border of two different areas of cultural assimilation implications developed in the community. Tendency blend of Javanese and Islam reflected in the current market in Wonosari Village and patterns of behavior of individuals who sought not in conflict with prevailing social values. This study aims to determine the underlying culture of economic behavior faced with the rationalization of neoclassical economics. The method used to explore and explain the economic decisions through qualitative research methods with the paradigm of phenomenology, given the Wonosari Village believes strongly in the local social and cultural values that influence patterns of behavior in interaction. Results of the study found that there is some value in line with neoclassical economic rationalization, where all things in economic interactions must be for-profit, and there is also contrary to the values of economic rationalization. The conclusion to be drawn is the value of a good adherence to the parents and to the specific role turned out in line with the rationalization of the economy rests on the efficiency to obtain profit maximization. But there is also a value that is not in line with economic rationalization that is in adherence to religious values and local culture, which prefers good relations between people rather than the profit motive.Keywords: rationality economy, culture